Biodiversity of the scentless plant bugs (Hemiptera: Rhopalidae) in southern South America - Melo, María Cecilia (2016)
This paper provides a comprehensive faunal survey of the Rhopalidae from southern South America with emphasis on the fauna of Argentina, based on published and unpublished data. The biodiversity from Argentina comprises 38 recorded species from six genera: Arhyssus Stål 1870 (one species), Liorhyssus Stål 1870 (two species), Niesthrea Spinola 1837 (five species), Xenogenus Berg 1883 (two species), Harmostes Burmeister 1835 (20 species), and Jadera Stål 1862 (eight species). We established accurate distributions for most of the species and report new distributional information for 27 of them. Most of these records are from Argentinean provinces, but we also report five new country records: three from Argentina – Harmostes (Harmostes) splendens Harris 1944, H. (Neoharmostes) bergi Göllner-Scheiding 1998 and Arhyssus tricostatus (Spinola 1852); one from Brazil – Xenogenus picturatum Berg 1883; and one from Paraguay – Harmostes (Harmostes) gravidator (Fabricius 1794).